Efforts to Improve Student Learning Outcomes on Fasting in the Month of Ramadan Using the Problem Based Learning Model at Lamsayuen State Elementary School - Ardiana; Emi Nurwati (Journal of Indonesian Primary School, 2025)
This research aims to improve student learning outcomes in the material of understanding fasting in the month of Ramadan in the subject of Islamic Religious Education through the application of the Problem Based Learning model. The research is a Class Action Research carried out in class V-A SD Negeri Lamsayuen, Ingin Jaya District, Aceh Besar Regency, for the 2024/2025 school year. The subjects of the study were all students of class V-A (N = 21). Data was collected through observation, learning outcome tests, documentation, and field notes. The pre-cycle results showed that only 5 students or 25% achieved the Minimum Completeness Criteria (KKM). After the implementation of the action in the first cycle, the completeness increased to 11 students or 50% with an average class of 68.09. The improvement of learning carried out in cycle II, including the variety of teaching materials, strengthening group discussions, and better classroom management, resulted in 20 students or 95% who achieved KKM with an average grade of 92.14. Qualitative analysis showed an increase in the activeness, motivation, and ability of students to understand the concept of fasting. These findings show the effectiveness of PBL in improving the achievement of learning outcomes and student involvement in fasting materials. This study recommends the integration of PBL with good classroom management as well as continuous evaluation and teacher training to sustain continuous learning improvement.